If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2a + -4) = m Reorder the terms: (-4 + 2a) = m Remove parenthesis around (-4 + 2a) -4 + 2a = m Solving -4 + 2a = m Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2a = 4 + m Combine like terms: -4 + 4 = 0 0 + 2a = 4 + m 2a = 4 + m Divide each side by '2'. a = 2 + 0.5m Simplifying a = 2 + 0.5m
| -q+5=10 | | p+.30p=666666667 | | K-3k+3=11 | | 9y^2-y= | | -y-3=8 | | 7d-13=17+3d | | 3(x+1)-7=20 | | 4x^2+7x=0 | | -x+100=100 | | 7(v+17)=6v | | -m+2=1 | | 3a+(2-2a)=a+2 | | -7=-c-29 | | x^2-9x+7=0 | | -5t^2+60t= | | -b+6=-16 | | 4(z-5)+2=z+3 | | 6x^2-22xy-12Y^2=0 | | 16x^5y^3+36x^3y^5= | | -(-3x+w)-4(2w+4x)= | | (3x+4)-(x+3)=3x+2+5x | | 8x+6=-9 | | y^2-2.309y+1=0 | | 3(3+X)=4(x-20) | | 10(a+1)=130 | | .25x=39000 | | 28=5a-2 | | m+4= | | 10x+3(3-x)=44 | | 6-2(h+3)=2h+12 | | 8-y+4y=-13 | | 21-(x+8)=4x-7 |